The Tao of Pooh - Hoff, Benjamin 1946- (London Mandarin Paperbacks, 1989)
Explains the basic concepts of the Chinese philosophy of Taoism through a discussion of how Winnie-the-Pooh lives by its principles.
The how of Pooh? -- The tao of who? -- Spelling Tuesday -- Cottleston pie -- The Pooh way -- Bisy Backson -- That sort of bear -- Nowhere and nothing -- The now of Pooh.
"A Mandarin paperback."
Keywords: Milne, A.A. -- 1882-1956 -- Characters -- Winnie the Pooh; Milne, A.A. -- 1882-1956 -- Religion; Children -- Books and reading -- Great Britain -- History -- 20th century; Children's stories, English -- History and criticism; Winnie-the-Pooh (Fictitious character); Teddy bears in literature; Taoism in religion; Taoism